A Prophetic Law Approach to Reconciling Indonesia’s Uneasy Relationship with Cross-border Surrogacy - Heriyanto, Dodik Setiawan Nur; Ulvi Gasimzadeh (Prophetic Law Review, 2024)
The modernization of reproductive technology has made things easier for couples who are not yet blessed with children. Currently, the practice of surrogacy has been successful in providing children through surrogate mothers. Abroad, this practice can cross national borders, where the surrogate mother can come from a different nationality than the child's prospective parents. This practice is done to get good genes or offspring according to their hopes, especially if the couple rents a womb from a European or East Asian race. Two legal issues are studied in this research, namely those related to the legal status of the practice of surrogacy, which is cross-border according to private international law and Prophetic Law. Apart from that, this research also examines the urgency of regulating the practice of surrogacy in Indonesian law. This research, using a normative legal research methodology, concludes that even though the practice of surrogacy is considered legal based on private international law, from an Islamic Law perspective, this practice is strictly prohibited (Haram) because it obscures the child's lineage status. The law in Indonesia really needs to regulate the legal vacuum related to the surrogate mother practice both domestically and across national borders to ensure legal certainty.